Mapping Pre-Modern Sicily Maritime Violence, Cultural Exchange, and Imagination in the Mediterranean, 800-1700 - Sohmer Tai, Emily; Reyerson, Kathryn L. (Mediterranean Perspectives, 2022)
XXVII, 346 p. 45 illus.